(untitled) - Streitferdt, Uwe (Hauppauge, N.Y., 1994)
this book explains complex scientific and medical terms in plain language. All common canine diseases are covered.
Keywords: Dogs,Dogs,Dogs; Diseases,Diseases,Homeopathic treatment,Health